Water pollution & management - Malik, D.S
Water Pollution and Management reflects the impact assessment of point and non-point pollution sources in water quality, analysis of water quality index, biological and pollution indicators, metallic contamination and their distribution and public health hazards aspects. The book provides a comprehensive study of water pollution in relation to its ecological context together with the antecedents along with human health and suggestive strategies for water management, control and regulation working polices for safe drinking, agriculture and industrial utilization etc. The book forms a significant contribution for research scientist, aqua culturists, environmentalists and researchers engaged in the field of water pollution, control and management.